2010
DOI: 10.1016/j.fct.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea purpurea extracts modulate murine dendritic cell fate and function

Abstract: Echinacea is a top-selling herbal remedy that purportedly acts as an immunostimulant. However, the specific immunomodulatory effects of Echinacea remain to be elucidated. We focused on defining the effects of Echinacea purpurea extracts in dendritic cells (DCs), which generate innate and adaptive immune responses. We hypothesized that E. purpurea extracts would enhance murine bone marrow-derived DC (BMDC) activation leading to increased immune responses. The fate and function of DCs from C57Bl/6 mice was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Differential effects on human DC maturation in vitro was observed for various Echinacea purpurea extracts, with increased expression of CD83 by the root and flower extracts whereas whole plant and stem/leaf extracts reduced this expression [45]. This effect was further supported by another study of E. purpurea root and leaf extracts, where the polysaccharide-rich root extracts increased and the alkylamide-rich leaf extract inhibited murine DC marker expression [46]. The ability of plant-derived medicines to exhibit pleiotropic DC functions underlines the inherent complexity in understanding the biological properties of these preparations.…”
Section: Modulation Of Dendritic Cell Activitymentioning
confidence: 50%
“…Differential effects on human DC maturation in vitro was observed for various Echinacea purpurea extracts, with increased expression of CD83 by the root and flower extracts whereas whole plant and stem/leaf extracts reduced this expression [45]. This effect was further supported by another study of E. purpurea root and leaf extracts, where the polysaccharide-rich root extracts increased and the alkylamide-rich leaf extract inhibited murine DC marker expression [46]. The ability of plant-derived medicines to exhibit pleiotropic DC functions underlines the inherent complexity in understanding the biological properties of these preparations.…”
Section: Modulation Of Dendritic Cell Activitymentioning
confidence: 50%
“…Few investigators have examined the mechanism of Echinacea polysaccharide action on the immune system and very few have undertaken comparative studies. Benson et al have shown that the polysaccharide-rich root extract increased the expression of MHC class II, CD86, and CD54 while the alkylamide-rich leaf extract inhibited expression of both [21]. Thude et al using flow cytometry showed that a polyclonal antibody to a glycoprotein, arabinogalactan-protein, from E. purpurea not only bound leukocytes extensively and non- specifically, but also did not interact with either CD4 or CD8 receptors [49].…”
Section: Discussionmentioning
confidence: 99%
“…Generally ethanol extracts are expected to contain higher levels of alkylamides and phenolic compounds, while aqueous extracts contain more hydrophilic compounds such as polysaccharides and glycoproteins. Polysaccharides, glycoproteins, and cichoric acid have been identified as having immune-stimulating activity [11,20,21] in contrast to alkylamides and ketones that appear to be anti-inflammatory in vitro and in vivo [22-24]. Purified polysaccharide extracts from Echinacea increased macrophage chemotaxis, production of reactive oxygen intermediates (ROS), and inhibited growth of fungi in vivo [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been widely used as CHM. The polysaccharide-rich root water extract of Echinacea purpurea (L.) Moench increased the expression of MHC II, CD86, and CD54 and the production of IL-6 and TNF-α in BM-DCs (Benson et al, 2010). Polysaccharides from Astragalus mongholicus Bunge, Achyranthes bidentata Blume and Rehmannia glutinosa (Gaertn.)…”
Section: Polysaccharide Of Chmmentioning
confidence: 98%